Description of the entomofauna associated with the remains of the Cistercian nun Angela Veronica Bava (1591-1637) - Vanin, Stefano; Boano, Rosa; Giordani, Giorgia; Carta, Giuseppina; Fulcheri, Ezio (Medicina Historica, 2022)
The study of insects and other arthropods from death bodies is commonly used in forensic contexts but, in the last years this approached is also applied to archaeological contexts where cadavers - human or other animals – are found. Insects provides a large spectrum of information that is used to reconstruct the peri and post mortem events. In this paper the evidence produced by insects collected from the remains of the nun Angela Veronica Bava is used to describe the taphonomic process of the body and to verify historical data. Diptera and Coleoptera fragments were collected from the body. Diptera belong to Hydrotaea capensis (Muscidae), whereas Coleoptera are included in 5 different families Zopheridae, Carabidae, Dermestidae, Staphylinidae and Endomychidae. Entomological evidence is in agreement with the historical data highlighting that the entomological approach can be properly carried out in archaeological studies related with religious contexts.